Comparative primate socioecology - Lee, Phyllis C. (Cambridge studies in biological and evolutionary anthropology, 1999)
Comparative studies have become both more frequent and more important as a means for understanding the biology, behaviour and evolution of mammals. Primates have complex social relationships and diverse ecologies, and represent a large species radiation. This book draws together a wide range of experts from fields as diverse as reproductive biology and foraging energetics to place recent field research into a synthetic perspective. The chapters tackle controversial issues in primate biology and behaviour, including the role of brain expansion and infanticide in the evolution of primate behavioural strategies. The book also presents an overview of comparative methodologies as applied to recent primate research which will provide new approaches to comparative research. It will be of particular interest to primatologists, behavioural ecologists and those interested in the evolution of human social behaviour